PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT.PERKEBUNAN NUSANTARA VI UNIT USAHA BUKIT CERMIN KABUPATEN SAROLANGUN - Etty Siswati (Universitas Batanghari Jambi, 2016)
This study aims 1. To determine the influence of the working environment on PT. Perkebunan Nusantara VI Unit Usaha Bukit Cermin Sarolangun. 2. To know the effect of work discipline in PT. Perkebunan Nusantara VI Unit Usaha Bukit Cermin Sarolangun 3. To determine the influence of the working environment and work discipline on employee performance on PT. Perkebunan Nusantara VI Unit Usaha Bukit Cermin Sarolangun.The collecting methods of data used is survey methods used to obtain information from respondents by using technic interviews and distribute a list of questions and by using a Likert scale. This study population on employees on. PT. Perkebunan Nusantara VI Unit Usaha Bukit Cermin Sarolangun was 60 peoples.The analysis tool used is multiple linear regression and this method using computer assistance through the program SPSS 20.0 for windows. From the calculation results SPSS 20.0 was obtained tcount for the Working Environment variable is equal to 5,589 and significance value (Sig.) is 0,000. If to comparison is found tcount> ttabel or 5,589> 167,203.It can be concluded that the work environment influence significantly to employee performance on PT. Perkebunan Nusantara VI Unit Usaha Bukit Cermin Sarolangun. tcount for work discipline variable is equal to 3,636 and with a significance value (Sig.) is 0.001. If to comparison is found tcount> ttabel or 3,636> 167.203. It concluded that the Working discipline variables influence significantly to employee performance on PT. Perkebunan Nusantara VI Unit Usaha Bukit Cermin Sarolangun.Fcount equal to 36.154 with a significance value (Sig.) is 0,000. If to comparison Fcount> Ftable or 36.154 > 3.190. It concluded that the working environment and work discipline simultantly have a significant effect on employee performance on PT. Perkebunan Nusantara VI Unit Usaha Bukit Cermin Sarolangun.Keywords: Work Environment, Work Discipline, Performance Employee